Food and feed production strategies for Vertisols in the Ethiopian highlands - Tedla, A.; Asamenew, G. (International Board for Soil Research and Management, 1993)
Since 1986 the Joint Vertisol Project (JVP) which involved a number of national and international research and Development institutions in Ethiopia gave high priority to developing alternative management practices for increased and sustainable food and feed production in highland vertisols. The JVP chose the highland areas because Ethiopian smallholders are already using draught animal technology and the availability of large vertisol areas. Research led to the Development of a broadbed maker (BBM) by connecting two traditional of-drawn mareshas. With the use of BBM a ploughed land can be shaped in the form of broadbed and furrows (BBFs) to improve drainage of excess water from vertisols. Drained seed bed opens up opportunities for alternative cropping systems. These alternatives were conceptualised in hypothetical model. This paper presents the results of the cropping systems tested on few drained vertisols as envisaged in the same model.